Clinical Outcome of Patients with Advanced Biliary Tract Cancer in a Dedicated Phase I Unit. Issue 3 (March 2018) - Sundar, R.; Custodio, A.; Petruckevich, A.; Chénard-Poirier, M.; Ameratunga, M.; Collins, D.; Lim, J.; Kaye, S.B.; Tunariu, N.; Banerji, U.; de Bono, J.; Lopez, J.
Abstract: Aims: Advanced biliary tract carcinomas (ABC) are malignancies with limited effective therapies for advanced disease. There is little published evidence of outcomes of ABC patients participating in phase I clinical trials. Materials and methods: Patient characteristics, treatment details and outcomes of ABC patients treated at a dedicated phase I unit were captured and analysed from case and trial records. Results: In total, 123 ABC patients were included in the study, of which 48 patients participated in 41 different phase I trials; 75 (61%) did not participate due to rapid disease progression or patient choice. Molecular characterisation of tumours using a targeted panel was conducted in 15 (31%), yielding several potentially actionable mutations, including BRCA, PIK3CA, FGFR, AKT and PTEN loss. Of the 39 evaluable patients there was one exceptional responder. Eighteen (46%) other patients achieved stable disease as their best response, with a clinical benefit rate at 4 months of 10%. Treatment was generally well tolerated with grade 3 or 4 adverse events only observed in eight patients (17 %), of which six were drug related and led to trial discontinuation in one (3%), with no toxicity-related deaths. Conclusion: Carefully selected ABC patients have been found to tolerate experimental phase I clinical trials without excess toxicity. The aggressive nature of this disease warrants consideration of early referral to a phase I unit. Future work will require comprehensive molecular profiling in an attempt to understand the biology underlying the exceptional responders and to match patients in real-time to targeted therapies. Highlights: Advanced biliary tract cancer patients do not have excessive toxicities on phase I trials. An exceptional response to a novel agent is described with biological rationale. Molecular profiling may help match patients to novel agents with potential benefit.